Impoliteness in Indonesian Language Hate Speech on Social Media Contained in the Instagram Account - Subyantoro, Subyantoro; Apriyanto, Sigit (JOURNAL OF ADVANCES IN LINGUISTICS, 2020)
The phenomenon of hate speech is very interesting to draw. This is related to various recent events that have caused unrest in the community. Hate speech is an expression that stimulates people from certain social groups that are oriented toward differences, race, national origin, religion, and gender. The hate test in this study is seen from the perspective of the impoliteness theory. The research uses forensic theory, while the methodology uses qualitative. The data used, as many as 40 comments were used as research objects. Realization of hate speech based on impoliteness, there are 3 strategies, namely positive impoliteness strategies, negative impoliteness strategies, and satire or scoffing strategies. In other words, linguistic hate speech can be sent in the form of words, phrases, clauses, sentences, and in the form of discourse.